Leading by example: considerations for photo sharing - Rutledge, Kim (Wildlife Rehabilitation Bulletin, 2022)
<span style="color: #000000; font-family: -apple-system, BlinkMacSystemFont, 'Segoe UI', Roboto, Oxygen, Ubuntu, Cantarell, 'Fira Sans', 'Droid Sans', 'Helvetica Neue', sans-serif; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">As wildlife rehabilitators, we have unique access to wildlife and valid reasons to photograph or otherwise document our patients, including public education, case management, volunteer recruitment, and fundraising. While an experienced wildlife rehabilitator understands the context when viewing images of wild patients, the general public does not. To avoid misrepresenting the field of wildlife rehabilitation and unintentionally condoning the mistreatment of wildlife, it is our responsibility to carefully and thoughtfully curate photos, videos, and other depictions of the animals in our care.